A cluster randomized trial of a comprehensive intervention nesting family and clinic into school centered implementation to reduce myopia and obesity among children and adolescents in Beijing, China: study protocol - Xinxin Wang; Jiajia Dang; Jieyu Liu; Yunfei Liu; Yaqi Wang; Di Shi; Ziyue Chen; Wen Yuan; Shan Cai; Jie Mi; Pei Xiao; Li Li; et al. (BMC, 2023)
Abstract Background Myopia and obesity in children and adolescents have become serious public health problems that endanger public health, especially in China. Unhealthy lifestyle behaviors are environmental drivers of both myopia and obesity. This protocol describes a study to evaluate the effectiveness of "22510SS", that is 2 h of daytime outdoor activities ('2'); Limit screen time to no more than 2 h per day ('2'); Consume at least 5 servings of fruits and vegetables daily ('5'); Attain 1 h of physical activity daily ('1'); Consume 0 sugar-sweetened beverages ('0'); Reasonable sleep duration ('S'); Regular supervision ('S'). A school-based, multifaceted intervention strategy for myopia and obesity prevention, and to assess and explore the implementation of "22510SS" with regards to acceptability, feasibility, adoption, usage and maintenance. Methods and analysis This study aims to develop a comprehensive intervention strategy "22510SS" based on the socio-ecological model, and A two-arm cluster randomized trial with a parallel-group of a 1:1 allocation ratio in 36 primary and secondary schools to test its evidence-based intervention programs on the effects and implementation of myopia and obesity epidemics in children and adolescents in grades 4 and 7. The primary outcomes will include differences in visual acuity, body mass index, outdoor activity indicators, screen time, fruit and vegetable intake, high-quality protein intake, sugar-sweetened beverage intake, sleep duration, and level of monitoring among children and adolescents. Secondary outcomes will assess the acceptability, feasibility, uptake, use, and maintenance of the intervention. Effects on the primary and secondary outcomes will be analyzed using linear and logistic regression analyses, as well as difference-in-difference analysis, taking into account cluster effects and possible confounding factors. Process assessments will also be conducted through quantitative and qualitative analyses, including acceptability, feasibility, gender, adoption, implementation, and sustainability. Discussion This study will evaluate the effectiveness of "22510SS" and examine its implementation in the school-based network nesting family and clinic. Following this intervention study, the integrated intervention program focused on myopia and obesity among children and adolescents have great potential to be implemented in China to promote and support healthy lifestyle behavior change and reduce the risk of myopia and obesity in children and adolescents. Trial registration NCT05275959. Registered 23 Mach 2022.